Mitochondrial-Derived Peptides in Diabetes and Its Complications - Wu, Ying; Sun, Liankun; Zhuang, Zhoudao; Hu, Xiaoqing; Dong, Delu (Frontiers in Endocrinology, 2022)
The changes of mitochondrial function are closely related to diabetes and its complications. Here we describe the effects of mitochondrial-derived peptides (MDPs), short peptides formed by transcription and translation of the open reading frame site in human mitochondrial DNA(mtDNA), on diabetes and its complications. We mainly focus on MDPs that have been discovered so far, such as Humanin(HN) mitochondrial ORF of the 12S rDNA Type-c (MOTS-c) and Small humanin-like peptides(SHLP 1-6), and elucidated the role of MDPs in diabetes and its major complications stroke and myocardial infarction by improving insulin resistance, inhibiting inflammatory response and anti-apoptosis, providing more possibilities for the clinical application of mitochondria derived peptides.